Effects of Mountain Uplift and Climatic Oscillations on Phylogeography and Species Divergence of Chamaesium (Apiaceae) - Zheng, Hong-Yi; Guo, Xian-Lin; Price, Megan; He, Xing-Jin; Zhou, Song-Dong (Frontiers in Plant Science, 2021)
Exploring the effects of orographic events and climatic shifts on the geographic distribution of organisms in the Himalayas-Hengduan Mountains (HHM) region and Qinghai-Tibetan Plateau (QTP) is crucial to understand the impact of environmental changes on organism evolution. To gain further insight into these processes, we reconstructed the evolutionary history of nine Chamaesium species distributed across the HHM and QTP regions. In total, 525 individuals from 56 populations of the nine species were analyzed based on three maternally inherited chloroplast fragments (rpl16, trnT-trnL, and trnQ-rps16) and one nuclear DNA region (internal transcribed spacer, ITS). Fifty-two chloroplast DNA (cpDNA) and 47 ITS haplotypes were identified in nine species. All of the cpDNA and ITS haplotypes were species-specific. Phylogenetic analysis suggested that all nine species form a monophyletic clade with high bootstrap support. Dating analysis and ancestral area reconstruction revealed that the ancestral group of Chamaesium originated in the southern Himalayan region at the beginning of the Paleogene (60.85 Ma). The nine species of Chamaesium then separated well during the Miocene, creating the nine species known today. Our maxent modeling indicated the broad-scale distributions of all nine species remained fairly stable from LIG to the present and predicted that it will remain stable into the future. The initial split of Chamaesium was triggered by climate changes following the collision of the Indian plate with the Eurasia plate during the Eocene. Subsequently, divergences within Chamaesium may have been induced by the intense uplift of the QTP, the onset of the monsoon system, and Central Asian aridification. Long evolutionary history, sexual reproduction, and habitat fragmentation could contribute to the high level of genetic diversity of Chamaesium. The higher genetic differentiation among Chamaesium populations may be related to the drastic changes of the external environment in this region and limited seed/pollen dispersal capacity.